The Application of Lean Thinking to Enhance the Efficiency of Performance Review Process to Select Good Practices of Faculty of Liberal Arts, Prince of Songkla University - Saelim, Bannagorn (Thammasat Journal, 2025)
This research aimed to investigate the efficiency of the performance review process to identify good practices within the Faculty of Liberal Arts, Prince of Songkla University, by employing Lean Thinking as a tool to enhance its effectiveness. The began with the use of a Flow Process Chart to assess the current workflow, followed by analyzing problems using 5W1H method and improvement guidelines based on the ECRS principle. Lastly, a new work process was presented using Value Stream Mapping (VSM). Data analysis was conducted using frequency and percentage. The study revealed substantial process improvements that the number of process activities decreased from 112 to 46, a reduction of 66 activities or 58.93%. Working hours were shortened from 3,035 minutes to 730 minutes, a decrease of 2,305 minutes or 75:95%. Paper usage was reduced from 503 pieces to 12 pieces, a reduction of 491 pieces or 97.61%. Finally, the cost of paper usage dropped from 236.41 baht to 5.64 baht, a reduction of 230:77 baht or 97.61%. This research indicated that applying information technology to work processes significantly enhanced work efficiency.